miR-8-3p regulates mitoferrin in the testes of Bactrocera dorsalis to ensure normal spermatogenesis - Tariq, Kaleem; Metzendorf, Christoph; Peng, Wei; Sohail, Summar; Zhang, Hongyu (Scientific reports, 2016)
Genetics-enhanced sterile insect techniques (SIT) are promising novel approaches to control Bactrocera dorsalis, the most destructive horticultural pest in East Asia and the Pacific region. To identify novel genetic agents to alter male fertility of B. dorsalis, previous studies investigated miRNA expression in testes of B. dorsalis. One miRNA, miR-8-3p was predicted to bind the 3′UTR of putative B. dorsalis mitoferrin (bmfrn). The ortholog of bmfrn in D. melanogaster is essential for male fertility. Here we show that bmfrn has all conserved amino acid residues of known mitoferrins and is most abundantly expressed in B. dorsalis testes, making miR-8-3p and mitoferrin candidates for genetics-enhanced SIT. Furthermore, using a dual-luciferase reporter system, we show in HeLa cells that miR-8-3p interacts with the 3′UTR of bmfrn. Dietary treatments of adult male flies with miR-8-3p mimic, antagomiR, or bmfrn dsRNA, altered mitoferrin expression in the testes and resulted in reduced male reproductive capacity due to reduced numbers and viability of spermatozoa. We show for the first time that a mitoferrin is regulated by a miRNA and we demonstrate miR-8-3p as well as bmfrn dsRNA to be promising novel agents that could be used for genetics-enhanced SIT.
Gesehen am 20.5.2020